Acetylshikonin induces apoptosis of human osteosarcoma U2OS cells by triggering ROS-dependent multiple signal pathways. (February 2023) - Cha, Hyo Sun; Lee, Han Ki; Park, See-Hyoung; Nam, Myeong Jin
Abstract: Acetylshikonin a natural compound isolated from the root of Lithospermum erythrorhizon and one of the shikonin derivatives which possess promising anticarcinogenic ability. In this study, we attempted to investigate the anti-cancer potential of acetylshikonin towards osteosarcoma U2OS cells. The effects of acetylshikonin towards the treatment of U2OS cells showed that decreased cell proliferation and inhibited migration ability of cells which are experimentally assessed via wide range of assays including MTT, WST-1, cell counting, colony formation assays, wound healing assay and gelatin zymography assay. We also observed that early apoptosis and late apoptosis were increased through fluorescence-activated cell sorter (FACS) analysis. Terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick-end labeling (TUNEL) assay showed that acetylshikonin induced DNA fragmentation. Western blot analysis revealed the apoptotic effect of acetylshikonin by measuring of proteins such as cleaved caspase −9, −8, −3, −6, −7, and Bcl-2 family. We observed that ROS level and DNA damage were increased via DCF-DA assay and comet assay. In terms of the presence of ROS, induction of apoptosis was detected by measuring proteins such as cleaved caspase 3, PARP, Bcl-2 and Bax. We suggested that the reactions were related to the nuclear translocation of FOXO3 through western blot of cytoplasmic/nuclear protein fractionation. We finally demonstrated that the knockdown of the FOXO3 induced the decrease of the apoptosis-associated proteins via western blot of FOXO3 siRNA transfection. Taken together, these results suggested that acetylshikonin might induce ROS-mediated apoptosis in a FOXO3-dependent manner against osteosarcoma cells. Therefore, acetylshikonin may be elucidated as an effective candidate for the treatment of osteosarcoma. Highlights: Acetylshikonin a natural compound possess anticarcinogenic properties. Evaluation of anticarcinogenic effect of acetylshikonin towards human osteosarcoma cells. Acetylshikonin might induce ROS-mediated apoptosis in a FOXO3-dependent manner against osteosarcoma cells.